1995
DOI: 10.1002/bbpc.19950990108
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Nonanoic Acid Monolayer Adsorbed at the Hg/Aqueous Solution Interface: Influence of Conformational Freedom in Bulk Aqueous Solution

Abstract: The adsorption of the nonanoic acid at the electrified Hghqueous solution interface is studied by means of capacity and surface tension measurements. Comparison of the experimental r,,, value with the calculated more favoured solvated conformation suggests that the acid is adsorbed in a partially coiled conformation. The adsorption free energy here determined, together with previously reported values found in the literature concerning other saturated acids and alcohols, is compared with reactivity and calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…A smooth decay is always observed, leading ultimately to a limiting value of ∼4.3 μF cm -2 , which is typical of densely packed monolayers of functionalized alkyl chains such as alkanethiols 6,10 and fatty alcohols . Similar differential capacity transients have been reported for the adsorption of nonanoic acid and a series of ω -mercaptocarboxilyc acids 19 on mercury and n -alkanethiols on gold . We have observed that down to a value of ∼12 μF cm -2 C d decreases linearly with t 1/2 and its slope is proportional to the MHOL concentration, suggesting that the deposition process is governed by the mass transport from the solution.…”
Section: Resultssupporting
confidence: 80%
“…A smooth decay is always observed, leading ultimately to a limiting value of ∼4.3 μF cm -2 , which is typical of densely packed monolayers of functionalized alkyl chains such as alkanethiols 6,10 and fatty alcohols . Similar differential capacity transients have been reported for the adsorption of nonanoic acid and a series of ω -mercaptocarboxilyc acids 19 on mercury and n -alkanethiols on gold . We have observed that down to a value of ∼12 μF cm -2 C d decreases linearly with t 1/2 and its slope is proportional to the MHOL concentration, suggesting that the deposition process is governed by the mass transport from the solution.…”
Section: Resultssupporting
confidence: 80%
“…Despite the electrostatic nature of the repulsion among the adsorbed K222 molecules, the adsorption driving force remains the usual mechanism of hydrophobic repulsion of the exposed molecular surface, common with aliphatic compounds. In fact, the value of Δ G 0 / kT per unitary cross section surface is 26 nm -2 , to be compared with the value of 28 nm -2 as obtained from data on aliphatic alcohols and acids reported in ref (Table 4).…”
Section: Resultsmentioning
confidence: 90%
“…These characteristics, along with the very high affinity of mercury toward a variety of organic molecules, make it an ideal substrate for assembling pinholes-free SAMs. Accordingly, condensed films of substances such as fatty acids [14][15][16], alcohols [17][18][19][20], quinolines [21], uracil derivatives [22,23], phospholipids [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] etc. have been formed on Hg and studied using, in particular, capacity as well as voltammetric measurements.…”
Section: Introductionmentioning
confidence: 99%